RECOMMENDATIONS TO IMPROVE EMPLOYEE PERSONAL ATTITUDE TOWARD REPORTING PATIENT SAFETY INCIDENTS - Purwo Andari; Candra Ferdian Handriyanto; Nyoman Anita Damayanti; Widodo Jatim Pudjirahardjo (Jurnal Administrasi Kesehatan Indonesia)
Background: Patient Safety Incidents (PSI) in hospitals are adverse events that need to be reported for effective identification and risk management, aiming to prevent reoccurrence of incidents. However, not all incidents are documented, as evidenced by the discrepancy in the number of phlebitis reported by employees as well as Infection IPCLN at three hospitals.